Effects of maternal vitamin B12 supplementation on early infant neurocognitive outcomes: a randomized controlled clinical trial. Issue 2 (29th June 2016) - Srinivasan, Krishnamachari; Thomas, Tinku; Kapanee, Aruna Rose Mary; Ramthal, Asha; Bellinger, David C.; Bosch, Ronald J.; Kurpad, Anura V.; Duggan, Christopher
Abstract: Maternal nutritional status during pregnancy impacts fetal brain development. Vitamin B12 plays a vital role in neuronal development. However, findings from studies on the association between maternal B12 status and child cognitive functions have been inconsistent. We performed a randomized, placebo‐controlled clinical trial of oral B12 supplementation (50 µg) beginning at <14 weeks of gestation through a 6‐week post‐partum. In the present study, we report the effects of maternal B12 supplementation on cognitive development in infants at 9 months of age on Bayley Scales of Infant Development‐III (BSID‐III). One hundred eighty‐three pregnant women received vitamin B12, and 183 received placebo. Nine‐month BSID‐III development score was available in 178 infants. There were no significant differences in maternal sociodemographic characteristics and baseline biochemical measures between infants who underwent BSID‐III evaluation and infants who were not evaluated. There were no significant differences in any of the subscales of BSID‐III between infants born to mothers who received B12 supplementation ( n  = 78) vs. placebo ( n  = 100). On multiple regression analysis, elevated maternal total homocysteine (tHcy) levels adjusted for treatment group, birthweight, parity, income and home environment at second trimester of pregnancy were significantly negatively associated with expressive language (β = 3.13 points, P  < 0.001), and in third trimester of pregnancy with expressive language (β = −2.29 points, P  < 0.001) and fine motor (β = −1.41 points, P  = 0.005) domains of BSID‐III. While no significant effects of maternal B12 supplementation were seen on cognitive development in infants at 9 months of age, elevated maternal tHcy levels were associated with poorer cognitive performance in some of the subdomains of BSID‐III. In pregnant women with elevated tHcy levels and or B12 deficiencies, it may be worthwhile to study the impact of longer term maternal supplementation on infant cognitive outcomes.